An Enhanced DCO-OFDM Scheme for Dimming Control in Visible Light Communication Systems - Yang Yang; Zhimin Zeng; Julian Cheng; Caili Guo (IEEE Photonics Journal)
In visible light communication (VLC) systems, optical orthogonal frequency-division multiplexing (O-OFDM) is an appealing modulation scheme. Recently, a number of O-OFDM schemes have been proposed. Among them, direct-current O-OFDM (DCO-OFDM) is a widely used scheme for its high spectral efficiency and low complexity. Since VLC involves a combination of illumination and communication, different optical power is often required to achieve a certain illumination level. However, clipping noise will dominate a severe performance degradation of DCO-OFDM when a relatively high or low illumination level is imposed, and it restricts applications of DCO-OFDM in future VLC systems. To address this problem, an enhanced DCO-OFDM (eDCO-OFDM) scheme is proposed. By introducing a piecewise function with adaptive slopes according to the required optical power, the proposed eDCO-OFDM scheme has the potential to effectively eliminate the clipping noise. Furthermore, two parameter selection mechanisms with different complexities and performance gains are designed for the piecewise function in the eDCO-OFDM scheme. Simulation results verify the energy and spectral efficiency of the proposed scheme under the constraints of optical power.